(untitled) - Hughes, Richard L. (Boston, 2009)
Leadership: Enhancing the Lessons of Experience, 6/e consists of 13 chapters and three leadership skills sections integrated into the text. Authors Hughes, Ginnett, and Curphy draw upon three different types of literature—empirical studies; interesting anecdotes, stories and findings; and leadership skills—to create a text that is personally relevant, interesting, and scholarly. The authors’ unique quest for a careful balancing act of leadership materials helps students apply theory and research to their real-life experiences. The Sixth Edition has been thoroughly updated in virtually every chapter.
Keywords: Leadership,Sự lãnh đạo